Gender Ideology: an analysis methodology - Jasmine Moreira; Maria Rita de Assis César (Universidade Federal do Rio Grande do Sul, 2019)
This paper proposes a two-step model for the inference of discourse on textual databases. The focus is on gender ideology and the action of EscolasemPartido.org and the Free Brazil Movement (Movimento Brasil Livre) on social networks, as well as the presence of the debate on the subject in the Chamber of Deputies. The first stage consists of a discourse analysis, made from the contributions of Michel Foucault and Judith Butler. The second stage consists of verifying the materiality of discourse in selected documents, using a topic modeling method based on latent Dirichlet allocation - LDA. It is concluded that the methodology allows one to infer the presence of the discourse of gender ideology on social networks, driving its reception by the parliamentary debate.